2020
DOI: 10.1073/pnas.2002835117
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the broad substrate specificity of two acyl-CoA dehydrogenases FadE5 from mycobacteria

Abstract: FadE, an acyl-CoA dehydrogenase, introduces unsaturation to carbon chains in lipid metabolism pathways. Here, we report that FadE5 from Mycobacterium tuberculosis (MtbFadE5) and Mycobacterium smegmatis (MsFadE5) play roles in drug resistance and exhibit broad specificity for linear acyl-CoA substrates but have a preference for those with long carbon chains. Here, the structures of MsFadE5 and MtbFadE5, in the presence and absence of substrates, have been determined. These reveal the molecular basis for the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Recently, Chen et al (2020) reported that FadE5 from Mtb and Msm contributed to drug resistance. 64 Our lipidomics data set showed a significantly lowered production of mycolic acids (Figure 5D and Table 2). This is consistent with our prior observation (Figure 1) that a treatment with either DA-CB or ETH was associated with similar global metabolomics changes, which, in turn, suggests a shared general MoA that includes disrupting mycolic acid biosynthesis.…”
Section: Integration Of Lipidomics and Proteomics Data Demonstrates D...mentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, Chen et al (2020) reported that FadE5 from Mtb and Msm contributed to drug resistance. 64 Our lipidomics data set showed a significantly lowered production of mycolic acids (Figure 5D and Table 2). This is consistent with our prior observation (Figure 1) that a treatment with either DA-CB or ETH was associated with similar global metabolomics changes, which, in turn, suggests a shared general MoA that includes disrupting mycolic acid biosynthesis.…”
Section: Integration Of Lipidomics and Proteomics Data Demonstrates D...mentioning
confidence: 83%
“…Acyl-CoA dehydrogenases introduce unsaturation into the carbon chains during lipid metabolism, which correlates with the observed accumulation of unsaturated fatty acids in cells treated with DA-CB. Recently, Chen et al (2020) reported that FadE5 from Mtb and Msm contributed to drug resistance …”
Section: Resultsmentioning
confidence: 99%
“…The fixA-fixB gene products probably participate in FAO-related electron transport (39). The fadE5 is likely involved in β-oxidation of the acyl side chain of cholesterol (40), and a recent study showed broad specificity of FadE5 for acyl-CoAs (41). The icl encodes multifunctional isocitrate lyase/methylisocitrate lyase required for both the glyoxylate shunt and the methylcitrate cycle (15,42).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, in this study, fadE5 gene demonstrated consistent down-regulation of RNA transcript and protein level in both stress and exponential growth conditions of the hypervirulent M. tuberculosis H112. The fadE5 of M. tuberculosis plays a role in the catabolism of fatty acids, particularly in the long-chain carbon substrates used for lipogenesis in pathogenic mycobacteria [ 30 ]. The regulation of abundance and chain length of the virulence-related lipids is vital for the impermeability of the mycobacterial cell envelope because overactive fatty acids catabolism is detrimental to the pathogenicity and growth of the mycobacteria [ 31 ].…”
Section: Discussionmentioning
confidence: 99%